Implementasi pendidikan karakter pada mata pelajaran pendidikan pancasila materi norma dalam kehidupan kelas v sekolah dasar - Shasfi Annisa; Rukayah Rukayah; Supianto Supianto (Didaktika Dwija Indria, 2024)
This study intends to demonstrate how character education is implemented in Pancasila Education on the topic of norms in life in class V SDN Kleco II Surakarta, as well as the challenges that stand in the way of its implementation and potential solutions. This type of research is qualitative. Teachers and fifth-graders served as the research subjects at SDN Kleco II Surakarta. Data collection techniques in this study used interviews, observations, and document studies. Data validity testing techniques used were source triangulation and technique triangulation. The data analysis technique used was an interactive model developed by Miles and Huberman. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of character education through Pancasila Education was carried out through three stages, namely planning, implementation, and evaluation. The character values of religion, tolerance, discipline, creativity, curiosity, respect for achievement, and responsibility contained therein have been well implemented, but there are still some students who have not been able to apply them. The obstacles found are students who are bored when learning and the attitude of students towards material that has not been maximally implement, while the teacher is only focused on completing the material. The solution to overcome existing obstacles is for teachers to create innovative learning and use active learning approaches.